2018
DOI: 10.1159/000494273
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Growth Restriction and Hyperoxia as a Cause of White Matter Injury

Abstract: Intrauterine growth restriction (IUGR) is estimated to occur in 5% of pregnancies, with placental insufficiency being the most common cause in developed countries. While it is known that white matter injury occurs in premature infants, the extent of IUGR on white matter injury is less defined in term infants. We used a novel murine model that utilizes a thromboxane A2 (TXA2) analog (U46619), a potent vasoconstrictor, to induce maternal hypertension and mimic human placental insufficiency-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 58 publications
5
26
0
Order By: Relevance
“…In contrast to transient changes in OL populations in IUGR, IUGR with hyperoxia resulted in sustained OL alterations into adulthood. The combination of IUGR and hyperoxia also led to more pronounced WMI on MRI and gait changes in adult mice (Chang et al, 2018). The different findings seen with these perinatal exposures support a multi-hit hypothesis for WMI and also highlight that different mechanisms may be involved with each exposure.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…In contrast to transient changes in OL populations in IUGR, IUGR with hyperoxia resulted in sustained OL alterations into adulthood. The combination of IUGR and hyperoxia also led to more pronounced WMI on MRI and gait changes in adult mice (Chang et al, 2018). The different findings seen with these perinatal exposures support a multi-hit hypothesis for WMI and also highlight that different mechanisms may be involved with each exposure.…”
Section: Introductionmentioning
confidence: 69%
“…Existing animal studies of IUGR demonstrate evidence of oligodendroglial (OL) injury and subsequent WMI (Olivier et al, 2007;Tolcos et al, 2011;Volpe et al, 2011;Reid et al, 2012;Basilious et al, 2015;Rideau Batista Novais et al, 2016), specifically, a decrease in immature/pre-myelinating OLs and total OL population (Chang et al, 2018). This is similar to findings in models of prematurity and hypoxic-ischemic injury where blocked maturation of oligodendrocyte progenitor cells (OPCs) is implicated in impaired white matter development (Chang et al, 2018). Despite these cellular changes, the molecular mechanisms remain incompletely understood.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Although Verhagen et al similarly reported poorer cognition at r c SO 2 levels above 83% on day 1, Verhagen et al (20) the inverse relationship between r c SO 2 and PIQ is puzzling. PIQ has, however, been related to motor function, and oxidative stress is known to cause white matter and motor neuron injury, in particular if preceded by hypoxia (36)(37)(38)(39)(40)(41). Additionally, hemodynamic redistribution may occur within the brain from frontal regions to basal ganglia in FGR fetuses with brainsparing and impending cardiac failure, as heralded by abnormal DV waveforms (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%